Education in Medieval Bengal: An Account of Two Systems (Philosophy and Progress, 2024)
In the medieval Bengal, Hindus and Muslims lived in a society where mainly the religion controlled foremost aspects of life. In this context, both the communities maintained two distinct educational systems in Bengal. This paper attempts to present the emergence of Islamic education in Bengal during Sultanate period and its development in relation to the indigenous education of the Hindus. It also examines interactions of Islamic education with its Hindu counterpart from Sultani to Nawabi period despite having clear distinctions across the communities in many respects. Analyzing the primary and secondary sources on education of Medieval Bengal, this paper shows how in a religiously polarized society, the Hindus and Muslims interacted in the field of education going beyond the existing hostility, mistrust and prejudices in many aspects of their distinctive life styles.Philosophy and Progress, Vol#73-74; No#1-2; Jan-Dec 2023 P 37-57